Determination and comparison of selected heavy metal concentrations in seawater and sediment samples in the coastal area of Suva, Fiji. (August 2020) - Arikibe, Joachim Emeka; Prasad, Surendra
Abstract: The coastal area of Suva, Fiji is exposed to high degree of metals input from different sources such as land-based industrial activities like metal fabrication and construction, paint manufacturing, petroleum storage and garment manufacturing, food processing and fish cannery as well as activities of bottling plants. It is therefore essential to have continuous monitoring and environmental management for the coastal area. Thus, to assess the degree of contamination of metals, selected metals (Cd, Zn, Pb, Cu and Ni) concentrations were analysed in seawater and sediment samples collected from ten sites in the coastal area of Suva, Fiji. The concentration of these metals in the samples was analysed using flame atomic absorption spectrometer (FAAS). The concentrations of the metal in seawater were in the range: 0.23–0.80 mg/L, 0.08–1.45 mg/L, 0.15–0.25 mg/L, 0.88–1.77 mg/L and 0.88–10.29 mg/L for Ni, Zn, Cd, Pb and Cu, respectively. The corresponding concentrations of metal in the sediment samples in dry weight (dw) basis for Ni, Zn, Cd, Pb and Cu were in the range: 17.24–28.74 mg/kg, 18.55–68.78 mg/kg, 5.49–9.16 mg/kg, 116.96–233.92 mg/kg and 78.43–490.18 mg/kg, respectively. The quality of the seawater was evaluated with respect to WHO established guidelines while the quality of the sediments evaluated using internationally accepted Sediment Quality Guidelines (SQGs). The contamination of the sediments was also assessed in terms of geo-accumulation index (Igeo ), contamination factor (Cf ) as well as pollution load index (PLI). Zn complied with the guidelines in all ten sites, Cu in eight sites was within the guidelines while Ni complied with the guideline in six sites. However, the levels of contamination recorded for Cd and Pb in all ten sites did not comply with the guidelines.